Translation Teaching and Cognitive Linguistics - Termina, Baaziz (Research in Language, 2020)
This paper is mainly concerned with the implications of cognitive linguistics for translation teaching and pedagogy. It sets out to succinctly chart some presumed shortcomings of replacement-based pedagogical methods that have long been centred around linear mechanical substitution of linguistic signs and patterns. Replacement approach, the paper argues, falls short of reinforcing what it takes to be the conceptual competence. In this connection, we account for our main assumption that translation teaching should be based on a sound theoretical footing that takes the conceptual system and the frames, or other structuring entities, populating it on board. Experimentally focusing on the conceptual system, cognitive linguistics’ framework, we contend building on some relevant literature, provides a wide range of far reaching procedural models conductive to the innovation of translation pedagogy and practice. The examples investigated in the paper reveal that translation teaching may be more prolific if it is equally based on such models, which inform our understanding of textual lexico-semantic units in terms of their surface functioning as prompts serving for dynamically constructing semantic-conceptual equivalence.